ANALISIS PENGARUH ECONOMIC VALUE ADDED (EVA), MARKET VALUE ADDED (MVA), PRICE TO BOOK VALUE (PBV), EARNING PER SHARE (EPS), PRICE EARNING RATIO (PER), DAN PROFITABILITAS TERHADAP RETURN SAHAM LQ 45 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2010 – - ,; , (Bilancia : Jurnal Ilmiah Akuntansi; Vol 3 No 4 (2019): Bilancia : Jurnal Ilmiah Akuntansi, 2019)
The purpose of this research is to analyze the influence of economic value added, market value added, price to book value, earnings per share, price earning ratio, and profitability on return  stock’s LQ 45. This research uses purposive sampling method to determine the sample. The sample in this study is a company listed on the Indonesia Stock Exchange during 2010-2018 with a total of 9 corporate samples. The analysis technique used is multiple linear regression analysis. The result of this study shows that economic value added, price to book value, earning per share, price earning rasio, and profitabilitas influence significantly on stock return’s LQ 45 while market value added does not influence significantly on stock return’s LQ 45 listed in the Indonesia Stock Exchange from 2010 to 2018. Tujuan dalam  penelitian ini  untuk menganalisis pengaruh variabel economic value added, market value added , price to book value, earning per share, price earning rasio , dan Profitabilitas (ROE)TerhadapReturn SahamLQ 45. Penelitian ini mengunakan metode Purposive sampling untuk menentukan sampelnya.Sampel dalam penelitian ini adalah perusahaan yang terdaftar di Bursa Efek Indonesia selama 2010-2018 dengan jumlah 9 sampel perusahaan. Teknik analisis yang digunakan adalah analisis regresi linear berganda. Hasil analisis menunjukkan bahwa economic value added , price to book value , price earning rasio , Profitabilitas   berpengaruh signifikan terhadap return saham LQ 45, Sedangkan  market value added tidak berpengaruh signifikan terhadap return saham LQ 45.